The Relationship of Body Mass Index and Diabetic Foot Risk in Type 2 Diabetes Mellitus at Royal Prima Hospital on Period 2018 to 2020 - Emori Christina Simarmata; Tasya Armadinah; Yeni Puspawani; Juliana Lina (Archives of The Medicine and Case Reports, 2021)
Body mass index (BMI) is a simple method that is commonly used to determine whether a person is obese or not. Diabetes mellitus is a disorder of the metabolic system because the pancreas cannot produce enough insulin or the body's cells cannot use insulin effectively. Diabetic foot is one of the chronic complications of diabetes mellitus (DM). Diabetic foot begins with hyperglycemia which causes abnormalities in neuropathy and blood vessels, causing infection. To determine the proportion of body mass index in patients with diabetes mellitus, to determine the prevalence of diabetic feet and non-foots. The research design used in this study is observational analytic. There is a relationship between body mass index and the risk of diabetic foot in type 2 DM patients at Royal Prima Hospital. Prevalence of body mass index 23. 0 in DM Type 2 at Royal Prima Hospital Medan in 2018-2020 reached 70%. The prevalence of diabetic foot in Type 2 DM at the Royal Prima Hospital Medan in 2018-2020 reached 54%.